The hero with a thousand faces - Campbell, Joseph, 1904-1987; Joseph Campbell Foundation (Novato, California : New World Library, 2008)
Since its release in 1949, The Hero With a Thousand Faces has influenced millions of readers by combining the insights of modern psychology with Joseph Campbell's revolutionary understanding of comparative mythology. In these pages, Campbell outlines the Hero's Journey, a universal motif of adventure and transformation that runs through virtually all of the world's mythic traditions. He also explores the Cosmogonic Cycle, the mythic pattern of world creation and destruction.
Part II: The cosmogonic cycle. 1: Emanations. From psychology to metaphysics ; The universal round ; Out of the void--space ; Within space--life ; The breaking of the One into the Manifold ; Folk stories of creation -- 2: The virgin birth. Mother universe ; Matrix of destiny ; Womb of redemption ; Folk stories of virgin motherhood -- 3: Transformations of the hero. The primordial hero and the human ; Childhood of the human hero ; The hero as warrior ; The hero as lover ; The hero as emperor and as tyrant ; The hero as world redeemer ; The hero as saint ; Departure of the hero -- 4: Dissolutions. End of the Microcosm ; End of the Macrocosm -- Epilogue: Myth and society. The shapeshifter ; The function of myth, cult and meditation ; The hero today.
Includes bibliographical references (pages 363-382) and index.
Keywords: Mythology; Jungian psychology